Cardiovascular disease prevalence and risk factor prevalence in Type 2 diabetes: a contemporary analysis. Issue 6 (10th October 2018) - McGurnaghan, S.; Blackbourn, L. A. K.; Mocevic, E.; Haagen Panton, U.; McCrimmon, R. J.; Sattar, N.; Wild, S.; Colhoun, H. M.
Abstract: Aims: To describe the prevalence of major cardiovascular disease (CVD) and risk factor control in a contemporary population with Type 2 diabetes. Methods: We used data from the national registry in Scotland, Scottish Care Information‐Diabetes, linked to hospital admissions. Using descriptive statistics and logistic regression we described associations of risk factors with CVD. CVD was defined based on diagnostic codes in primary or secondary care data for ischaemic heart disease, cerebrovascular disease peripheral arterial disease, heart failure, cardiac arrhythmia, hypertensive heart disease and revascularization procedures. Results: Among 248 400 people with Type 2 diabetes with a median age of 67.5 years (IQR 58.2, 76.1) and median diabetes duration of 7.8 years (3.8, 13.0), 32% had prior CVD (35% of men, 29% of women). Median HbA1c overall was 55 mmol/mol (7.2%), median SBP was 132 mmHg, median total cholesterol was 4.1 mmol/l and mean BMI was 32 kg/m 2 . Overall two‐thirds (65% of men, 68% of women) have two or more of the following CVD risk factor thresholds: HbA1c ≥ 53 mmol/mol (7%), SBP > 130 mmHg or DBP > 80 mmHg, total cholesterol ≥ 5 mmol/l or BMI ≥ 30 kg/m 2, or were currently smoking. Overall 84% were taking anti‐hypertensives and 75% a statin. Use of metformin was common at 58%, but other diabetes drugs that reduce CVD were rarely used. Conclusions: There continues to be a high prevalence of CVD among people with Type 2 diabetes and a high level of unmet need for risk factor control. This implies substantial scope for reducing the excess risk of CVD in diabetes through improved management of known risk factors. What's new?: There have been substantial advances in the management and prevention of cardiovascular disease in diabetes. To understand where unmet needs lie, it is important to understand the current burden of cardiovascular disease and the levels of treated and untreated risk factors. In this paper, we show that there continues to be a high prevalence of cardiovascular disease among people with Type 2 diabetes and a high level of unmet need for risk factor control. This implies substantial scope for reducing the excess risk of cardiovascular disease in diabetes through improved management of known risk factors.